Current Status and Future Directions of Bacteria-Based Immunotherapy - Tang, Quan; Peng, Xian; Xu, Bo; Zhou, Xuedong; Chen, Jing; Cheng, Lei (Frontiers in Immunology, 2022)
With the in-depth understanding of the anti-cancer immunity, immunotherapy has become a promising cancer treatment after surgery, radiotherapy, and chemotherapy. As natural immunogenicity substances, some bacteria can preferentially colonize and proliferate inside tumor tissues to interact with the host and exert anti-tumor effect. However, further research is hampered by the infection-associated toxicity and their unpredictable behaviors in vivo. Due to modern advances in genetic engineering, synthetic biology, and material science, modifying bacteria to minimize the toxicity and constructing a bacteria-based immunotherapy platform has become a hotspot in recent research. In this review, we'll go over the inherent advantages of unedited bacteria, highlight how bacteria can be engineered to provide greater tumor-targeting properties, enhanced immune-modulation effect, and improved safety. Then we summarized the successful applications of engineered bacteria in cancer immunotherapy or as part of the combination therapy. In the end, we pointed out the future directions and potential opportunities of this emerging field.